The correlation between the double helix quantum wave in d-wave superconductors and human DNA - (:unkn) unknown (Polish Academy of Sciences, 2012)
The effective mass of the quasiparticles in a d-wave superconducting system has been calculated via magnetization measurements done by SQUID by using the advanced derivative method used in our previous works. Phenomenological analogy between the double helix quantum wave, which does exist within the primitive cell of the d-wave superconductor, and the human DNA was previously made. In this work, the numerical proof of the analogy mentioned has been realized by determining the magnitude of the attractive force of d-wave structure and comparing with the magnitude of the force that holds the double strand of human DNA that are both of the same order of 10-10 N. Moreover, the wavelength of the double helix quantum wave of the superconducting system corresponds to ultraviolet region of the electromagnetic spectrum that exactly coincides with the wavelength which is used for exciting the states in human DNA.